Preparation of La2Sn2O7, Mg2SnO4, and MgSn(OH)6 and their antiviral/antibacterial activities - Ryuju Kiribayashi; Kayano Sunada; Yasuhide Mochizuki; Toshihiro Isobe; Keiichi Kobayashi; Takeshi Nagai; Hitoshi Ishiguro; Akira Nakajima (Journal of Materials Science: Materials in Medicine)
Abstract In order to develop inorganic antibacterial and antiviral materials that function in the dark, we synthesized La2Sn2O7, Mg2SnO4, and MgSn(OH)6, which are compounds of La2O3 and MgO, which have solid basicity, and SnO2, which has the Mars-van Krevelen (MvK) mechanism. After obtaining each sample as a single-phase white powder through hydrothermal or coprecipitation method, their antibacterial and antiviral activities were evaluated with reference to ISO procedures in the dark for bacteria and viruses with different characteristics. The dependence of activity on the evaluation method suggested that, except for Mg2SnO4, the proximity or contact of the viruses or bacteria to the sample surface played an important role in activity. Comparison of the activity of each sample with those of the simple oxides of constituent elements, La2O3, MgO, and SnO2, clarified that pH, solid basicity, phosphate affinity, and the MvK mechanism contribute to antibacterial and antiviral activity. The extent of these contributions varied depending on the sample. The study results revealed that La2Sn2O7 not only exhibits high antibacterial and antiviral activity against bacteria and viruses in the dark; it also has the ability to decompose organic dyes under UV irradiation. This material might be used as a newly developed environmental purification material providing continuous antibacterial and antiviral effects day and night, able to clean surfaces during UV light exposure. Graphical Abstract